QUALIMETRIC QUALITY ASSESSMENT OF IODINE SUPPLEMENTS - F. S. Bazrova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2015)
The article discusses the new iodine-containing supplements (ID) derived from organic media collagenous animal protein (pork rind, carpatina and collagen) and protein concentrates brands SCANGEN and PROMIL C95. It is shown that the use of these proteins as carriers of iodine is due to the high content of the amino acids glycine and alanine, which correlates with the degree of binding of iodine objects. New additives in addition to the special focus improve rheological properties of foods, including texture, appearance and functional properties. To assess the quality'ID and selection of preferred option the proposed qualitative assessment and a systematic approach to consider all'ID as a system to allocate its elements, to justify the principles of its construction and the requirements imposed on it, to build a General decision tree. For the construction of complex criterion for assessing the quality'ID proposed procedure formalization based on selection and evaluation of individual indicators, the definition of the laws of their change, depending on the dose, duration and temperature of exposure, and functional efficiency. For comparative evaluation of single and calculation of group indicators all of them were reduced to a single dimension by introducing the dimensionless coefficients of adequately describing the analyzed indicators. The article presents the calculated values of single and group of indicators characterizing technological properties 'ID: the degree of binding of iodine, the binding rate of iodine, heat losses of iodine and basic functional and technological properties of meat stuffing systems (water-binding, moisture-holding, emulsifying capacity and emulsion stability), obtained by the introduction of stuffing in the system studied'ID. At the final stage is the selection of the best 'ID, on the basis of an assessment of group performance.